PDF The Influence of Islamic Business Ethics on the Behavior of Traditional Market Traders: A Case Study of Pamekasan Evening Market: Pengaruh Etika Bisnis Islam terhadap Perilaku Pedagang Pasar Tradisional: Studi Kasus Pasar Sore Pamekasan - Ahmad Sholihin; Dinul Koyyimah (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study aims to analyze the influence of Islamic business ethics on the behavior of traders at Pamekasan's Evening Market. Islamic business ethics emphasizes moral principles such as shiddiq (trustworthiness), amanah (trustworthiness), tabligh (prophetic conduct), fathanah (faithfulness), and istiqamah (steadfastness), which are oriented toward blessings, not merely material gain. The study employed a quantitative approach with simple linear regression analysis. The study population comprised 103 traders at Pamekasan's New Evening Market, with a sample size of 39 respondents selected using purposive sampling. Primary data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and t-tests for hypothesis testing. The results indicate that Islamic business ethics have a positive and significant influence on trader behavior, with a contribution value of 83%, categorized as